PENGARUH MORAL REASONING AUDITOR PEMERINTAH TERHADAP KUALITAS AUDIT (Studi pada Kantor BPK RI Perwakilan Provinsi Sulawesi Tenggara) - Dalli, Nasrullah; Sari, Ika Maya; Wandira, Viladelvia L (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
The purpose of the research is knowing the effect of the application of Moral Reasoning to Audit Quality at the BPK RI Representative Southeast Sulawesi Province. The methods of data analysis used in this research is descriptive analysis method and modestly linear regression analysis method. The method of data collection use is the method of questionnaires that as many as 40 people of all government auditors on BPK RI Representative Southeast Sulawesi Province. However, just as many as 36 questionnaires can be processed.                              The results for the coefficient of determination total Moral Reasoning government auditor to Audit Quality of R2 = 0.650. This number can be used to see the contribution of the Moral Reasoning government auditor to Audit Quality. The figure has meaning that the contribution of Moral Reasoning government auditor to Audit Quality is 65%, while the remaining 35% was obtained from the contribution of other factors Keywords : Moral Reasoning, Audit Quality